Effect of the Extent of Apical Enlargement on the Degree of Debridement of the Apical Third in Curved Root Canals - Andrabi, Syed Mukhtar-Un-Nisar; Kumar, Ashok; Tewari, Rajendra Kumar; Mishra, Surendra Kumar; Iftekhar, Huma; Zia, Afaf (UI Scholars Hub, 2018)
Objectives: The present study aimed to evaluate the influence of various apical instrumentation sizes and tapers on the degree of debridement of the apical third of curved root canals. Methods: We used 60 extracted human mandibular first molars with mesial root curvatures of 20° to 30°. In all teeth, access cavity preparation was performed, followed by coronal flaring with Gates Glidden drills #1–4 (Dentsply Maillefer). Specimen teeth were subsequently randomly divided into five groups (n = 12). Each group was enlarged to a particular apical size and taper as follows: no apical preparation done (group I, Control group); 25/.04 and 25/.06 (Group II); 30/.04 and 30/.06 (group III); 35/.04 (group IV); 40/.04 (group V). Specimens were rinsed with 17% EDTA and 3% NaOCl solutions. We used a scanning electron microscope to evaluate specimens’ degree of debridement. Retrieved data were analyzed using Kruskal–Wallis and Mann–Whitney U-tests (p < 0.05). Results: Acceptable debridement was observed in groups III, IV, and V. Additionally, debridement was significantly better in Groups IV and V than in group II. Conclusion: Apical preparation with <30/.04 size results in an unacceptable degree of debridement of the apical third.